EKSISTENSI LAHAN USAHATANI PADI DI KOTA MAKASSAR - Achmad, Rahmi; Jamil, Muh. Hatta; Rukka, Rusli M; Bulkis, Sitti; Rahmadanih, Rahmadanih; Amrullah, A. (Hasanuddin University, 2020)
ABSTRACTThe existence of rice farming in Makassar City is important because it contributes to the availability of food. This study examines various aspects that affect the existence of rice farming in Makassar City. Informants in this study were heads of farmer groups and government representatives. The analytical method used is qualitative descriptive whereas to know strategy priority need to maintain rice farming land used the Analytic Hierarchy Process (AHP) method with support Expert Choice software 11. Results of the study conclude that the existence of rice farming land in Makassar city can be seen physically with a land area of 2,636 hectares and through land use by people who still manage rice farming land. Strength factors for farming in rice farming land in Makassar City are agricultural products that are consumed for family food sources, as a source of income, incapable condition of the peasant, the selling price of land is low and farming land are families inheritance while the weakness factors of farmers are land ownership status, unproductive land conditions, inappropriate and undistributed of government supporting for farmer's needs,Â limited fertilizer availability, pest and plant disease and there is no regeneration to manage existing land; the strategy priority needed in maintaining rice farming land in Makassar City for farmers isÂ enhancement agricultural production facilities and infrastructureKeywords: Strategy; Rice; Agriculture.